(untitled) (International Journal of Engineering and Computer Science, 2015)
Query Recommendation for Interactive Database Exploration (QueRIE) is a recommendation system that supports interactive database exploration. The users who are not familiar with the database schema may face great difficulty in performing this job. This system aims at assisting non expert users of relational databases by generating personalized query recommendations. QueRIE tracks the querying behavior of previous users and identifies similar patterns. These similar query patterns are used to generate recommendations. There are three approaches used in this work for generating query recommendations viz., suggested query by dictionary mapping, tuple based and fragment history. And also the performance is analyzed among the three approaches.